PENGARUH LAPORAN ARUS KAS OPERASI, INVESTASI, PENDANAAN DAN LABA AKUNTANSI TERHADAP TINGKAT LIKUIDITAS PADA PT. SEMEN INDONESIA Tbk. TERDAPAT DI BURSA EFEK INDONESIA TAHUN (2013-2020) - Khoirina, Siti; Rini, Prima (Jurnal Manajemen dan Bisnis (JMB), 2022)
Abstract Â This research uses PT. Semen Indonesia Tbk. Which is listed on the Indonesia Stock Exchange (BEI) in the period 2013-2020. The data used is quantitative data obtained from the Indonesia Stock Exchange website www.idx.co.id. The population in this study amounted to 32 and sampling technique is time series. The purpose of this research is to prove empirically the influence of operating cash flow statements, investments, funding and accounting profit on liquidity level. From the analysis results show that based on testing simultaneously by using the test F all variables research operating cash flows, investment cash flows, cash flow financing, and accounting profit. By looking at the value of the influence of Fcount 6.536 and Ftabel 2.95 where Fcount is greater than Ftable 6.536> 2.95 and its influence level with Sig value 0.001 means less than 0.05. Based on partial test of t-test only operating cash flow which has no effect to see the value of influence where the value Tcount = 0.726 and Ttable = 1.699 which means Tcount is smaller than Ttable 0.726 <1.699 and the level of influence with significance value 0.474 which means greater than Level of significance of 0.05.